Work and family roles in relation to women's well-being: A longitudinal study - Noor, Noraini M. (Wiley, 1995)
Previous research on women has focus on the influence of the overall work- or family-role experiences rather than on the specific characteristics of each role. Using multi-dimensional measures of work- or family-role experiences, this study first examined (Time 1) the additive cumulative contributions of role experiences in the prediction of women's well-being (happiness and symptoms of psychological distress). While work overload significantly predicted distress at Time 2, none of the family-role variables was related to well-being. Second, as the sample was made up of two groups of women who differed in occupational status (secretaries and professional women), it was possible that the effect of overload on distress might be conditioned by occupational status. The group X overload interaction term was found to be highly significant (p<.007); high occupational status moderated the negative effects of work overload. By contrast, secretaries were adversely affected by work overload. These results are discussed in relation to the existing literature, with reference to women work and family roles in relation to women's well-being, and the effects of occupational status on helath outcomes.